Analisis Pengaruh Jumlah Wajib Pajak Terdaftar dan Jumlah SPT Terlapor terhadap Penerimaan Pajak Penghasilan KPP Pratama Rantau Prapat - Mutiara Zain Dalimunthe; Arnida Wahyuni Lubis (VISA: Journal of Vision and Ideas, 2023)
The purpose of the study was to determine the effect of the number of registered taxpayers and the number of reported annual tax returns on income tax revenues. This study uses qualitative methods, using interview and observation data collection techniques. The population in this study is the number of registered taxpayers and the number of reported tax returns for 2019-2021. The results showed that the number of taxpayers and the number of annual tax returns had a significant simultaneous effect on the income tax revenue of KPP Pratama Rantau Prapat. Keywords : Income Tax, Taxpayer, Annual Tax Return